Biodegradable nanoparticles induce cGAS/STING-dependent reprogramming of myeloid cells to promote tumor immunotherapy - Podojil, Joseph R.; Cogswell, Andrew C.; Chiang, Ming-Yi; Eaton, Valerie; Ifergan, Igal; Neef, Tobias; Xu, Dan; Meghani, Khyati A.; Yu, Yanni; Orbach, Sophia M.; Murthy, Tushar; Boyne, Michael T.; et al. (Frontiers in Immunology, 2022)
Cancer treatment utilizing infusion therapies to enhance the patient’s own immune response against the tumor have shown significant functionality in a small subpopulation of patients. Additionally, advances have been made in the utilization of nanotechnology for the treatment of disease. We have previously reported the potent effects of 3-4 daily intravenous infusions of immune modifying poly(lactic-co-glycolic acid) (PLGA) nanoparticles (IMPs; named ONP-302) for the amelioration of acute inflammatory diseases by targeting myeloid cells. The present studies describe a novel use for ONP-302, employing an altered dosing scheme to reprogram myeloid cells resulting in significant enhancement of tumor immunity. ONP-302 infusion decreased tumor growth via the activation of the cGAS/STING pathway within myeloid cells, and subsequently increased NK cell activation via an IL-15-dependent mechanism. Additionally, ONP-302 treatment increased PD-1/PD-L1 expression in the tumor microenvironment, thereby allowing for functionality of anti-PD-1 for treatment in the B16.F10 melanoma tumor model which is normally unresponsive to monotherapy with anti-PD-1. These findings indicate that ONP-302 allows for tumor control via reprogramming myeloid cells via activation of the STING/IL-15/NK cell mechanism, as well as increasing anti-PD-1 response rates.